Energy management handbook - Turner, Wayne C., 1942- (Fairmont Press, 2013)
This comprehensive handbook has become recognized as the definitive stand-alone energy manager's desk reference, used by thousands of energy management professionals throughout the industry. Newly revised and edited, this Eighth Edition includes significant updates to energy management controls systems, commissioning, measurement and verification, and high performance green buildings. Revised chapters cover motors and drives, HVAC systems, lighting, alternative energy systems, building envelope, performance contracting, and natural gas purchasing. Detailed illustrations, tables, graphs, and other helpful working aids are provided throughout. --